Monsoon wedding - Nair, Mira.; Baron, Caroline; Dhawan, Sabrina; Shah, Naseeruddin; Dubey, Lillete; Shetty, Shefali; Raaz, Vijay; Shome, Tillotama; Das, Vasundhara; Kharbanda, Kulbhusan; USA Films (Firm); IFC Productions (Firm); et al. (Universal City, CA : Universal, 2002)
Shot in New Delhi in 30 days, this film about a Punjabi wedding brings out all the frenzy and frolic, the loyalties, filial bonds and friendships, along with skeletons in the cupboard associated with such family events.
Special features: the making of "Monsoon wedding"; feature commentary with Mira Nair.
Naseeruddin Shah, Lillete Dubey, Shefali Shetty, Vijay Raaz, Tilotama Shome, Vasundhara Das, Kulbhushan Kharbanda.
MPAA rating: R.
DVD, 5.1 Dolby digital surround.
English, Hindi and Punjabi dialogue with English, Spanish, or French subtitles.
Closed-captioned for the hearing impaired.
Keywords: Comedy films; Feature films; Foreign films -- India; Films for the hearing impaired; Comedy films; Feature films; Films for the hearing impaired; Foreign films; India